Characterization of trabecular bone plate‐rod microarchitecture using multirow detector CT and the tensor scale: Algorithms, validation, and applications to pilot human studies - Saha, Punam K.; Liu, Yinxiao; Chen, Cheng; Jin, Dakai; Letuchy, Elena M.; Xu, Ziyue; Amelon, Ryan E.; Burns, Trudy L.; Torner, James C.; Levy, Steven M.; Calarge, Chadi A. (Medical physics (Lancaster), 2015)
Purpose: Osteoporosis is a common bone disease associated with increased risk of low‐trauma fractures leading to substantial morbidity, mortality, and financial costs. Clinically, osteoporosis is defined by low bone mineral density (BMD); however, increasing evidence suggests that trabecular bone (TB) microarchitectural quality is an important determinant of bone strength and fracture risk. A tensor scale based algorithm for in vivo characterization of TB plate‐rod microarchitecture at the distal tibia using multirow detector CT (MD‐CT) imaging is presented and its performance and applications are examined. Methods: The tensor scale characterizes individual TB on the continuum between a perfect plate and a perfect rod and computes their orientation using optimal ellipsoidal representation of local structures. The accuracy of the method was evaluated using computer‐generated phantom images at a resolution and signal‐to‐noise ratio achievable in vivo. The robustness of the method was examined in terms of stability across a wide range of voxel sizes, repeat scan reproducibility, and correlation between TB measures derived by imaging human ankle specimens under ex vivo and in vivo conditions. Finally, the application of the method was evaluated in pilot human studies involving healthy young‐adult volunteers (age: 19 to 21 yr; 51 females and 46 males) and patients treated with selective serotonin reuptake inhibitors (SSRIs) (age: 19 to 21 yr; six males and six females). Results: An error of (3.2% ± 2.0%) (mean ± SD), computed as deviation from known measures of TB plate‐width, was observed for computer‐generated phantoms. An intraclass correlation coefficient of 0.95 was observed for tensor scale TB measures in repeat MD‐CT scans where the measures were averaged over a small volume of interest of 1.05 mm diameter with limited smoothing effects. The method was found to be highly stable at different voxel sizes with an error of (2.29% ± 1.56%) at an in vivo voxel size as compared to the original ex vivo voxel size. Tensor scale measures derived from imaging under in vivo and ex vivo conditions with significantly different modulation transfer function, i.e., difference in “true resolution,” showed strong linear correlation (r = 0.92). The study of healthy volunteers shows that, after adjustment for height and weight, males have a 14% higher mean TB plate‐width as compared to females (p < 0.05). SSRI‐treated patients have 12.5% lower mean TB plate‐width (p = 0.052) as compared to age‐similar and sex‐, height‐, and weight‐matched healthy controls. In contrast, the observed group difference in dual‐energy x‐ray absorptiometry (DXA)‐derived hip BMD was 10.5% between males and females and only 5.04% between healthy controls and patients on SSRIs. Conclusions: Tensor scale analysis of MD‐CT images yields accurate and reproducible characterization of TB plate‐rod microarchitecture that may be more sensitive than DXA‐derived BMD to sex differences and to the skeletal changes associated with medical conditions or their treatments.